Ileocecal valve atresia with volvulus - Hicham Ajdar; Abdelhalim Mahmoudi; Othmane Alaoui; Khalid Khattala; Youssef Bouabdallah (Elsevier, 2022)
Atresia of the ileocecal valve is a very rare etiology of neonatal intestinal obstruction. We report the case of a newborn who presents a neonatal occlusion in whom the exploration has found a volvulus of the last intestinal loop and the cecum which were necrotic secondarily to atresia of the Bauhin valve. A resection ileocecal and ileocolic anastomosis have been realize.